Advertising model of mass media: evolution and modern transformation - Maevskaya, Elena V. (Journal of the Belarusian State University. Journalism, 2026)
This article examines the transition from the advertising-based media business model, which dominated for centuries, to a new, non-advertising model of modern media. Journalism, advertising, and the media are presented as closely interacting systems. The history of the advertising model’s formation, development, and evolution is traced, and the chronological framework of its existence is expanded. The cause of the current crisis of the traditional business model is identified – the digital transformation of media and the creative agency model. Changes in the balance of power among key players in the modern advertising and media market are analysed, as well as the increasing influence of conversational media and user-generated content. It concludes that the crisis of the advertising model has given rise to innovative forms of media practice, and the introduction of information technology has contributed to the mediatisation of advertising in particular and society as a whole.